Are stock markets influenced by sustainability matter? Evidence from European companies. (22nd August 2008) - Moneva, Jose M.; Ortas, Eduardo
The emergence of ethical investment is a sign of the increasing interest of shareholders in the impact of corporate activities on sustainable development. The objective of this article is to analyse the relationship between the sustainable performance of a company and its financial performance measured by stock market value. Belonging to the Dow Jones Sustainability Index, disclosing a Global Reporting Initiative Sustainability Report and Sustainable Ratings are used as proxies for sustainability. This article is based on sustainability as a multivariate issue, and exploratory factor analysis is used to model the sustainability performance of a sample of European companies.